From Marine Metabolites to the Drugs of the Future: Squalamine, Trodusquemine, Their Steroid and Triterpene Analogues - Kazakova, Oxana; Giniyatullina, Gulnara; Babkov, Denis; Wimmer, Zdenek (International journal of molecular sciences, 2022)
This review comprehensively describes the recent advances in the synthesis and pharmacological evaluation of steroid polyamines squalamine, trodusquemine, ceragenins, claramine, and their diverse analogs and derivatives, with a special focus on their complete synthesis from cholic acids, as well as an antibacterial and antiviral, neuroprotective, antiangiogenic, antitumor, antiobesity and weight-loss activity, antiatherogenic, regenerative, and anxiolytic properties. Trodusquemine is the most-studied small-molecule allosteric PTP1B inhibitor. The discovery of squalamine as the first representative of a previously unknown class of natural antibiotics of animal origin stimulated extensive research of terpenoids (especially triterpenoids) comprising polyamine fragments. During the last decade, this new class of biologically active semisynthetic natural product derivatives demonstrated the possibility to form supramolecular networks, which opens up many possibilities for the use of such structures for drug delivery systems in serum or other body fluids.
Keywords: Spermine; inhibitory angiogeneze; Cholestanes; trodusquemine; Humans; triterpenoids; neuroprotektivní látky; angiogenesis; squalamine; Antineoplastic Agents; spermin; Anti-Infective Agents; antiinfekční látky; Triterpenes; lidé; cholestanoly; Neuroprotective Agents; steroidy; Aquatic Organisms; cholestany; triterpeny; Angiogenesis Inhibitors; ceragenine; protinádorové látky; diabetes; claramine; biologické přípravky; antibiotic; vodní organismy; Steroids; obesity; Cholestanols; Biological Products